2020
DOI: 10.1152/japplphysiol.00655.2019
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide does not alter endurance exercise performance at 3,500-m altitude

Abstract: Acetazolamide (AZ) is a medication commonly used to prevent acute mountain sickness (AMS) during rapid ascent to high altitude. However, it is unclear whether AZ use impairs exercise performance; previous literature regarding this topic is equivocal. The purpose of this study was to evaluate the impact of AZ on time-trial (TT) performance during a 30-h exposure to hypobaric hypoxia equivalent to 3,500-m altitude. Ten men [sea-level peak oxygen consumption (VO2peak): 50.8 ± 6.5 mL·kg−1·min−1; body fat %: 20.6 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our findings are similar to those reporting negative effects of acetazolamide on exercise performance at altitude (Bradwell et al., 2014; Garske et al., 2003; Stager et al., 1990) and may be explained in part by a greater degree of metabolic acidosis induced by carbonic anhydrase inhibition (Garske et al., 2003; Jonk et al., 2007). However, we did not sample blood during the exercise protocol to document pH changes and are cautious over attributing the negative effects to acidosis in light of evidence that carbonic anhydrase inhibition does not interfere with skeletal muscle blood flow or gas exchange (Jonk et al., 2007), may have no effect on aerobic performance (Bradbury et al., 2020; Posch et al., 2018), or may even improve maximal oxygen consumption in hypoxia (Schoene, Bates, Larson, & Pierson, 1983). Also, while methazolamide has been shown to induce less muscular fatigue than acetazolamide in normoxia (Dominelli et al., 2018), effects of carbonic anhydrase inhibition on locomotor muscle fatigue at high altitude has been negligible (Fulco et al., 2006) and the net effect on aerobic exercise performance at altitude is inconclusive (Posch et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are similar to those reporting negative effects of acetazolamide on exercise performance at altitude (Bradwell et al., 2014; Garske et al., 2003; Stager et al., 1990) and may be explained in part by a greater degree of metabolic acidosis induced by carbonic anhydrase inhibition (Garske et al., 2003; Jonk et al., 2007). However, we did not sample blood during the exercise protocol to document pH changes and are cautious over attributing the negative effects to acidosis in light of evidence that carbonic anhydrase inhibition does not interfere with skeletal muscle blood flow or gas exchange (Jonk et al., 2007), may have no effect on aerobic performance (Bradbury et al., 2020; Posch et al., 2018), or may even improve maximal oxygen consumption in hypoxia (Schoene, Bates, Larson, & Pierson, 1983). Also, while methazolamide has been shown to induce less muscular fatigue than acetazolamide in normoxia (Dominelli et al., 2018), effects of carbonic anhydrase inhibition on locomotor muscle fatigue at high altitude has been negligible (Fulco et al., 2006) and the net effect on aerobic exercise performance at altitude is inconclusive (Posch et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, both drugs have side effects which limit their utility. For example, acetazolamide, a carbonic anhydrase inhibitor, induces metabolic acidosis, which may further impair aerobic performance at altitude (Garske, Brown, & Morrison, 2003; Jonk et al., 2007; Stager et al., 1990), although effects are often equivocal (Bradbury et al., 2020; Posch, Dandorf, & Hile, 2018). Dexamethasone, a glucocorticoid, can suppress adrenal function and increase the risk of bacterial, viral and fungal infections (Luks & Swenson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent placebo-controlled study, investigators found that 500 mg/day AZ did not alter endurance exercise performance in the form of 2 mile run time at 3,500 m altitude (Bradbury et al, 2020). In this context, however, these two recent publications did not attempt to clarify optimal dosing of AZ for rapid ascents to higher altitudes (Posch et al, 2018;Bradbury et al, 2020).…”
Section: Effects On Physical Performancementioning
confidence: 99%
“…Although the authors found that AZ more consistently caused impairments in aerobic exercise performance at sea level, there were more inconsistencies in the literature on the effects of AZ on exercise performance at altitude (Posch et al, 2018). In a more recent placebo-controlled study, investigators found that 500 mg/day AZ did not alter endurance exercise performance in the form of 2 mile run time at 3,500 m altitude (Bradbury et al, 2020). In this context, however, these two recent publications did not attempt to clarify optimal dosing of AZ for rapid ascents to higher altitudes (Posch et al, 2018;Bradbury et al, 2020).…”
Section: Effects On Physical Performancementioning
confidence: 99%
“…The most effective pharmacologic prophylaxis for AMS is acetazolamide (AZ), but it now appears that AZ use does not adversely affect athletic performance [8]; previous literature on this topic was inconclusive [9][10][11]. In a double-blinded trial evaluating AZ versus placebo, a strong correlation was found between PaO 2 and perfor-mance in 20 men ascending to 5000 m [12].…”
Section: Introductionmentioning
confidence: 99%